Identifying and ranking causal microbial biomarkers for colorectal cancer at different cancer subsites and stages: a Mendelian randomization study - Li, Hongfeng; Sheng, Dashuang; Jin, Chuandi; Zhao, Guoping; Zhang, Lei (Frontiers in Oncology, 2023)
Introduction The gut microbiome is directly involved in colorectal carcinogenesis, but much of the epidemiological evidence for the effect of the gut microbiome on colorectal cancer (CRC) risk comes from observational studies, and it is unclear whether identified microbial alterations are the cause or consequence of CRC development. Methods Univariate Mendelian randomization (MR) analysis and multivariate MR analysis based on Bayesian model averaging were performed to comprehensively explore the microbial risk factors associated with CRC. The Network Module Structure Shift method was used to identify microbial biomarkers associated with CRC. Mediation analysis was used to explore the dietary habits-microbiota-CRC pathway. Results The results of the four methods showed that 9 bacteria had a robust causal relationship with the development of CRC. Among them, Streptococcus thermophilus reduced the risk of CRC; Eubacterium ventriosum and Streptococcus were beneficial bacteria of malignant tumors of colon (CC); Erysipelotrichaceae was a protective factor for malignant tumors of rectal (CR); Bacteroides ovatus was a risk factor for benign tumors. Finally, the mediation analysis revealed 10 pathways by which dietary regulation bacteria affected the risk of CRC, including alcohol consumption increased the risk of CC by reducing the abundance of Eubacterium ventriosum (mediated proportion: 43.044%), and the mediated proportion of other pathways was 7.026%-34.22%. Discussion These findings will contribute to the understanding of the different carcinogenic mechanisms of intestinal flora in the colon and rectum and the risk of tumor transformation, thereby aiding CRC prevention, early screening, and the development of future strategies to reduce CRC risk.